2006
DOI: 10.1111/j.1365-2788.2006.00929.x
|View full text |Cite
|
Sign up to set email alerts
|

Personality, coping style and well‐being of parents rearing children with developmental disabilities

Abstract: Both adoptive and birth mothers and fathers used more problem-focused than emotion-focused strategies. Personality factors, Neuroticism especially, were predictive of coping strategy use. Higher levels of Positive Reappraisal were associated with higher levels of SWB, whereas higher levels of Escape-Avoidance were associated with lower levels of SWB, but only for mothers. Results were consistent with a dispositional model of strategy use in that frequency of use was associated with personality characteristics,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

21
176
2
8

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 157 publications
(207 citation statements)
references
References 40 publications
21
176
2
8
Order By: Relevance
“…In this study, mental burnout, were positively associated with seeking social support and self-controlling in Bedouin parents of children with ASD. As we know, coping by seeking support is associated with level of daily positive mood [29] and parents' subjective well-being [34]. Our results add Ways of coping and mental burnout of Bedouin mothers compared to Bedouin fathers of children with ASD implications of this study.…”
Section: Limitationssupporting
confidence: 52%
See 1 more Smart Citation
“…In this study, mental burnout, were positively associated with seeking social support and self-controlling in Bedouin parents of children with ASD. As we know, coping by seeking support is associated with level of daily positive mood [29] and parents' subjective well-being [34]. Our results add Ways of coping and mental burnout of Bedouin mothers compared to Bedouin fathers of children with ASD implications of this study.…”
Section: Limitationssupporting
confidence: 52%
“…This strategy may be associated with negative outcomes of stress [24] and depression [36]. Glidden [34] showed that accepting responsibility is negatively correlated with subjective well-being in parents of children with developmental disabilities. It is particularly important to investigate the determinants of this strategy due to its negative effects.…”
Section: Discussionmentioning
confidence: 99%
“…There is overwhelming support for this professional assistance in Glidden (2006), who reported that it is useful to get as much help as one can from professionals and other service providers. However, accessing such help tends to be difficult at times.…”
Section: Professional Support From Psychologists and Therapistsmentioning
confidence: 99%
“…It is useful to get as much help as one can from professionals and other service providers, which at times turn out to be difficult (Glidden, Billings & Jobe, 2006). The extent and type of needs may differ widely from one family to the other within the life cycle of the same family.…”
Section: Introductionmentioning
confidence: 99%
“…22 The importance of the well-being of families with children with disabilities has been explored by a number of researchers. 23,24 Families have been found to make decisions regarding placement that are in the interest of maintaining the highest level of functioning of all family members. 25 However, not all families balance the demands of caring for their child with a disability similarly, as the context of other family needs may differ.…”
Section: Reasons For Placement and Decision-makingmentioning
confidence: 99%